The impact of metropolises' characteristics on provincial economic structure transformation: Evidence from Vietnam - Bac Truong Cong (Cogent Economics & Finance, 2021)
Economic structure transformation is widely recognized as a crucial role in sustainable development. However, the existing literature almost focused on the change inside certain economic areas and ignored the external relationship. This raises the question about the role of factors outside in economic structure transformation at the prefecture-level. This paper takes Vietnam as the study area to fill this gap and examines the impact of metropolis's characteristics on the provinces' economic structural transformation. Using data of provincial economic structure from 2015 to 2018 collected from the General Statistics Office of Vietnam, the econometric analysis with instrument variables for panel data is performed. The results show that metropolises play an important role in the economic structure change of provinces through certain roles: destination of migration and start-point of remittances, the market for goods and services, hubs of information and knowledge.
Keywords: 330; Economic structure transformation; instrument variables; metropolis; prefecture-level; regional linkages; Vietnam